The effect of chronic ethanol ingestion on synthesis and degradation of soluble, contractile and stromal protein fractions of skeletal muscles from immature and mature rats. - Preedy, V R (1989)
1. An investigation was carried out into the response of soluble, myofibrillar and stromal protein fractions of skeletal muscle to chronic ethanol feeding. Groups of male Wistar rats, of approx. 85 or 280 g body wt., were pair-fed on a nutritionally complete liquid diet containing glucose or a diet in which 36% of the total energy was provided by ethanol. After 6 weeks, rates of protein synthesis were measured with a flooding dose of L-[4-3H]phenylalanine. 2. The protein contents of soluble, myofibrillar and stromal fractions in gastrocnemius muscle from small and large rats were decreased by ethanol feeding. Greater changes were observed in small than in large rats. 3. Fractional synthesis rates of soluble, myofibrillar and stromal proteins of gastrocnemius were all decreased by ethanol treatment. All fractions responded similarly, though percentage decreases in large rats were greater than in small rats. Absolute synthesis rates in gastrocnemius muscles were also decreased after ethanol treatment. All protein fractions responded similarly, and the magnitudes of the responses in large and small rats were also similar. 4. Fractional rates of breakdown, measured by the difference between fractional growth and synthesis rates, were apparently decreased, in both sets of rats, in all protein fractions. 5. It was concluded that chronic ethanol exposure causes perturbations in soluble, myofibrillar and stromal protein accretion by a mechanism involving unidirectional changes in protein synthesis and possibly breakdown.